Cannabidiol Drugs Clinical Trial Outcomes and Adverse Effects - Pauli, Christopher S.; Conroy, Matthieu; Vanden Heuvel, Brian D.; Park, Sang-Hyuck (Frontiers in Pharmacology, 2020)
This review aims to present completed clinical trial data surrounding the medicinal benefits and potential side effects of the increasingly popular cannabidiol (CBD)-based drug products, specifically Epidiolex. The article is divided into two sections based on if the ailment being treated by this cannabinoid is classified as either physiological or neurological conditions. In addition to describing the current status, we also examined the different primary and secondary outcomes recorded for each study, which varies greatly depending on the funding source of the clinical trial. With the recent FDA-approval of Epidiolex, this review mainly focused on trials involving this specific formulation since it is the only CBD-based drug currently available to clinicians, although all other clinically trialed CBD (A) drugs were also examined. We hope this review will help guide future research and clinical trials by providing the various outcomes measured in a single review.